Sistem Muzara'ah dalam Ekonomi Islam - Haris Faulidi Asnawi (Millah: Journal of Religious Studies, 2005)
This paper discusses how to process agricultural land according to muzdra'ah and the application of this system also its impact on social economy in society. From literature research looking at current condition of society, it was found that good co-operation between the land owner and the people working on the land are the key for this system. Both parties have to respect each other's right, not to harm the other party and avoid any behavior against the rule by owner’s area to his partner like stated in feudal system. The application of this system is usually seen in the people that are living in country side that depend on agricultural for living. This system is very helpful for farmers and land owners, which affecting their levels of friendship and their willingness to help each other, also opens opportunities of employment and eventually helps in increasing both parties’ income.